2010
DOI: 10.1016/s1658-3876(10)50036-0
|View full text |Cite
|
Sign up to set email alerts
|

Protein C levels in β-thalassemia major patients in the east Nile delta of Egypt

Abstract: Protein C plays a major role in the hypercoagulable state in thalassemic patients. These findings raise the issue as to whether it would be cost-beneficial to recommend prophylactic antithrombotic therapy in high-risk thalassemic patients. A wider prospective study is necessary to delineate under which circumstances therapy might be needed, and at what level of protein C deficiency to start prophylactic antithrombotic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
9
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 22 publications
6
9
1
1
Order By: Relevance
“…Significant reductions in PC and PS plasma activity and elevation of sEPCR were observed in nonsplenectomized compared with post splenectomy patients. In contrast to our results, Hassan et al reported significantly decreased PC and PS levels in splenectomized β-TM patients compared with controls [15] and Musumeci et al reported that the lowest PC and AT III levels were observed in older splenectomized patients [43]. Natesirinilkul et al found no significant differences in PC and PS levels in splenectomized and nonsplenectomized Hb E/β-thal patients [1].…”
Section: Tablecontrasting
confidence: 99%
See 2 more Smart Citations
“…Significant reductions in PC and PS plasma activity and elevation of sEPCR were observed in nonsplenectomized compared with post splenectomy patients. In contrast to our results, Hassan et al reported significantly decreased PC and PS levels in splenectomized β-TM patients compared with controls [15] and Musumeci et al reported that the lowest PC and AT III levels were observed in older splenectomized patients [43]. Natesirinilkul et al found no significant differences in PC and PS levels in splenectomized and nonsplenectomized Hb E/β-thal patients [1].…”
Section: Tablecontrasting
confidence: 99%
“…Previous studies have reported decreased PC and PS activity in β-TM [15,19,21] and Hb E/β-thal [22], and decreased PC in β-TI [23]. We observed a significant decrease of PC and PS activity in α-TI and α + β-thal and the PC deficiency was consistent with Type II abnormalities.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Decreased levels of protein C and protein S in thalassemic patients have been reported elsewhere. Hassan et al 8 reported decreased levels of protein C and S in their study of 50 children with thalassemia in comparison to the control group. 9 Sipahi et al 10 reported that protein C, protein S, and AT-III were low in 26.2%, 28.6%, and 46.8% of their thalassemic patients, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have reported high plasma D-dimers levels in TM patients that are enhanced after splenectomy. 8,17 Cappellini et al 3 reported normal plasma D-dimers levels in TM patients but higher levels in TI patients that were also most pronounced in splenectomized patients. In contrast, Naithani et al 18 reported similar D-dimers levels in b-thalassemic patients and controls.…”
Section: Discussionmentioning
confidence: 99%